Handbook for qualities of effective teachers - Stronge, James H. (Association for Supervision and Curriculum Development, 2004)
What makes an effective teacher? How do you help good teachers become even better? What tools and techniques are available to support and sustain quality teaching? In this companion to the best-selling Qualities of Effective Teachers, you'll find numerous strategies for examining the practice of teaching, helping teachers improve their skills, and establishing an environment that supports good teaching. Each chapter concentrates on a different aspect of teacher effectiveness, and the authors include real-life teacher scenarios with focus questions that prompt readers to analyze the specific qualities of teaching. The authors offer their own analyses of these scenarios and also include supportive research summaries, blackline masters, graphic organizers, and other aids to help readers thoroughly explore the various qualities of effective teachers. Principals, staff developers, teacher educators, teacher mentors, instructional leaders, and teachers themselves can use this book to ""support new teachers with emerging skills, ""coach promising teachers in the process of becoming effective teachers, and ""identify specific teacher needs, from questioning skills to assessment. No matter what the skill level of the teachers involved, Handbook for Qualities of Effective Teachers will encourage a new level of self-reflection and better focus efforts to develop the kind of teaching skills that make a positive difference in the classroom.